Analysis of factors associated with the non-use of modern contraceptive methods among multiparous women in Kisangani City, Democratic Republic of the Congo - Kitoko, E. W.; Mukandu, B. F.; Wembodinga, U. G.; Koto-Te-Nyiwa Ngbolua, Jean-Paul; Mawunu, M.; Mbungu, M. R. (Orapuh Journal, 2025)
IntroductionFamily planning is a cornerstone of women's reproductive health and plays a pivotal role in the socio-economic development of communities. The adoption of modern contraceptive methods (MCM) is critical for improving reproductive health and ensuring effective birth control. Despite its importance, the adoption of MCM remains limited in Kisangani City, Democratic Republic of the Congo, due to a range of sociodemographic, sociocultural, and socioeconomic factors.PurposeThis study aims to investigate the determinants of non-use of modern contraceptive methods among multiparous women in Kisangani, with a focus on understanding the barriers to adoption. By highlighting these determinants, the study seeks to contribute to global efforts to improve reproductive health interventions.MethodsData were collected between February and July 2024 from various health areas in the urban and rural communities of Kisangani. A sample of 811 women participated in the study. The data were entered and analyzed using SPSS software (version 21.0). Logistic regression analysis was employed to identify the factors significantly associated with the non-use of modern contraceptive methods. Odds ratios (OR) with p-values were calculated to determine the strength and significance of these associations.ResultsThe analysis revealed that several factors significantly influenced the non-use of modern contraceptive methods. Women belonging to non-Christian religions were less likely to use MCM (OR = 0.46, p = 0.00). A low level of education, either by the woman or her partner, was strongly associated with a higher likelihood of non-use (OR = 2.66 and 2.40, respectively, p = 0.00). Unemployed women were significantly more likely not to use MCM (OR = 2.37, p = 0.00), and unemployed spouses also influenced non-use (OR = 2.17, p = 0.00).ConclusionThe study reveals socio-demographic, cultural, and economic barriers hindering the use of modern contraceptives in Kisangani, particularly among women with low levels of education, those who are economically disadvantaged, and those belonging to certain religious groups. It recommends targeted strategies (education, economic empowerment, and tailored campaigns) to reduce unwanted pregnancies and improve women's reproductive health.